2011
DOI: 10.1007/s12598-011-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sample diameter on primary and secondary dendrite arm spacings during directional solidification of Pb-26wt.%Bi hypo-peritectic alloy

Abstract: The microstructure scales of dendrites, such as primary and secondary dendrite arm spacings, control the segregation profiles and the formation of secondary phases within interdendritic regions, which determine the properties of solidified structures. Investigations on primary and secondary dendrite arm spacings of primary α-phase during directionally solidified Pb-26wt%Bi hypo-peritectic alloy were carried out in this research, and systematic studies were conducted using cylindrical samples with different dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 29 publications
0
9
0
24
Order By: Relevance
“…the theoretical predictions are in good agreement with the experimental scatters of both hypoperitectic and hyperperitectic alloys. However, Hu et al 26 examined the growth of a Pb–26 wt- Bi hypoperitectic alloy under steady state DS solidification (Bridgman growth) for a wide range of growth rates (5×10 −3 to 5×10 −1 mm s −1 ) and have concluded that the predictions of the Hunt–Lu model are smaller and very far from the experimental evolution of λ 1 . Hu et al 25 have also carried out experiments of Bridgman growth with two hypoperitectic and two hyperperitectic Pb–Bi alloys and checked the experimental scatters of λ 1 against the theoretical predictions of the main steady state growth models from the literature: Hunt, 37 Kurz–Fisher 38 and Trivedi 39 models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the theoretical predictions are in good agreement with the experimental scatters of both hypoperitectic and hyperperitectic alloys. However, Hu et al 26 examined the growth of a Pb–26 wt- Bi hypoperitectic alloy under steady state DS solidification (Bridgman growth) for a wide range of growth rates (5×10 −3 to 5×10 −1 mm s −1 ) and have concluded that the predictions of the Hunt–Lu model are smaller and very far from the experimental evolution of λ 1 . Hu et al 25 have also carried out experiments of Bridgman growth with two hypoperitectic and two hyperperitectic Pb–Bi alloys and checked the experimental scatters of λ 1 against the theoretical predictions of the main steady state growth models from the literature: Hunt, 37 Kurz–Fisher 38 and Trivedi 39 models.…”
Section: Resultsmentioning
confidence: 99%
“…, the microstructure consisted of branched dendrites of a in a matrix of b, for intermediate values of G L .V L 21 aligned rods of a in a matrix of b, and for high values of G L .V L 21 , the microstructure was formed only by the phase b. Hu et al 15,[23][24][25][26] investigated the growth of Pb-Bi alloys having 26, 28 30 and 34 wt-% Bi using a Bridgman vertical apparatus with V L ranging from 5 to 500 mm s 21 at a constant G L of 20 K mm 21 . The observed microstructure is reported to be formed by dendrites of the primary a in a complex matrix of b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a variety of microstructures can be obtained from during solidification of peritectic alloys under non-equilibrium conditions, which depend mainly on the thermal parameters during solidification (thermal gradient, G L , growth rate, V L , and cooling rate, _ T) and the nucleation conditions. Possible microstructures include: cellular [4], bands [5,6], lamellar [7], eutectic type structures [8], and dendritic structures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and theoretical studies [1][2][3][4][5] have been carried out on peritectic solidification since many technologically important materials have been observed in peritectic systems. Recently, many studies on peritectic solidification have been carried out, and complex microstructures have been obtained, such as the dendritic/cellular growth of primary phase in the matrix of peritectic phase, coupled growth, 6,7 and banded structure.…”
Section: Introductionmentioning
confidence: 99%